2020
DOI: 10.3389/fpsyg.2020.596961
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Mobile Phone Problem Use in Bullying and Cyberbullying Among Adolescents

Abstract: Technology is being used by individuals of all ages; young children show a high tendency of problematic use of devices such as smartphones. This study aimed to identify different profiles that vary in conflicts related to problematic mobile phone use and maladaptive communication and emotional patterns. Therefore, we examined whether there are significant differences in bullying and cyberbullying among teenagers who have a problem utilizing mobile phones. The study participants were 810 students of Compulsory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
5
14
0
1
Order By: Relevance
“…Thus, it has been shown that emotional regulation is relevant in mobile phone use since those adolescents who had non-problematic use had adequate values compared to adolescents with moderately problematic use [18][19][20][21][22][23]. In addition, problematic mobile phone use has been associated with increased involvement in cyberbullying [40][41][42][43][44][45]. This is in line with research that suggests that the problematic use of new technologies is done to alleviate aggression or prevent impulsivity [32].…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Thus, it has been shown that emotional regulation is relevant in mobile phone use since those adolescents who had non-problematic use had adequate values compared to adolescents with moderately problematic use [18][19][20][21][22][23]. In addition, problematic mobile phone use has been associated with increased involvement in cyberbullying [40][41][42][43][44][45]. This is in line with research that suggests that the problematic use of new technologies is done to alleviate aggression or prevent impulsivity [32].…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, it has become clear that the problematic use of mobile phone is used as a tool to regulate emotions. Thus, the problematic use of mobile phones affects emotional intelligence and self-regulation, and therefore, the individual well-being and quality of life of adolescents [25], as well as interpersonal relationships, which manifests as bullying and cyberbullying situations [40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In its broadest sense, cyberbullying is any behavior that is performed using technology, particularly the internet, by an individual or group that involves repeatedly sending aggressive messages or other similar actions with the intention of causing harm [2]. Like traditional bullying, cyberbullying can have long-term effects for its adolescent victims [3], with technology being one of the most important risk factors [4].…”
Section: Introductionmentioning
confidence: 99%